1979
DOI: 10.1007/bf00234184
|View full text |Cite
|
Sign up to set email alerts
|

The location of LH-RH neurons in the rat hypothalamus and their pathways to the median eminence

Abstract: The location of the perikarya of LH-RH neurons in the rat hypothalamus and their pathways to the median eminence were studied by immunohistochemistry and radioimmunoassay after placing stereotaxic electrolytic lesions in several parts of the hypothalamus. The principal location of the cell somata was found to be in the ventral part of the medial preoptic area; their pathways were classified into a main baso-lateral pathway and an accessory descending pathway branching off from the former. The main pathway was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 18 publications
7
31
0
Order By: Relevance
“…This topography, very similar to that reported in guinea-pigs Setalo et al, 1976a ;Jennes and Stumpf, 1980), cats (Barry andDubois, 1974a, 1975) and rats (Naik, 1975a, b ;Setalo et al, 1976b ;Ibata et al, 1979), was obtained in young fetuses (60 and 70 days) and may therefore be different from adult distribution.…”
supporting
confidence: 89%
“…This topography, very similar to that reported in guinea-pigs Setalo et al, 1976a ;Jennes and Stumpf, 1980), cats (Barry andDubois, 1974a, 1975) and rats (Naik, 1975a, b ;Setalo et al, 1976b ;Ibata et al, 1979), was obtained in young fetuses (60 and 70 days) and may therefore be different from adult distribution.…”
supporting
confidence: 89%
“…These nerve processes projected to the lateral part of the external layer of the ME through the main baso-lateral pathway and the accessory descending pathway [11,13]. In the present study, these LHRH-LI nerve endings were observed to make intimate contact with GFAP-LI astrocytes in the subependymal cell layer and processes of tanycytes with GFAP-like immunoreactivity in the palisade layer of the ME.…”
Section: Discussionsupporting
confidence: 57%
“…From their location, therefore, one possibility that they may be involved in the regulation of release of the R/I H to the portal vessels is considered. Lutenizing hormone releasing hormone (LHRH) is a typical R/I H, and their nerve endings have been demonstrated in the pericapillary region of the ME and they show a specific regional distribution in the ME [11][12][13]16]. Therefore, it is of interest to elucidate their fine structural interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the perikarya of the LH-RH neurons are mainly located in the POSC. (Setalo et al, 1976, Ibata et al, 1979. From the present findings, it may be deduced that the noradrenergic pathway originating in the A1 supplies noradrenaline to the preoptic-anterior hypothalamic area, including the POSC, via the ventromedial tegmental area and the lateral hypothalamic area for the induction of proestrous gonadotropin surges.…”
Section: Resultssupporting
confidence: 52%